Perbandingan Hasil Belajar Matematika Antara Yang Menggunakan Pendekatan Konstruktivisme Dengan Pendekatan Open Ended - Avini Nurazhimah Arfa (Universitas Indraprasta PGRI Jakarta, 2018)
The purpose of this research is to know whether or not there are differences of learning outcomes of students of class X TKJ 1 and X TKJ 2 between those using a constructivism approach and those using an open-ended approach in learning mathematics in statistics chapter. The research method used is a quasi-experiment with population of students of SMK TERPADU HUTAMA and with samples of 68 people simply and randomly taken by using a self-developed instrument in the form of test about Mathematics Learning Outcomes. The research data for the experimental and controlled classes are collected by analyzing the test using t test, while the normality analysis requirement is analyzed by testing with chi-square test and homogeneity with F test. The result of the research shows that there is a significant difference between students’ learning outcomes through constructivism approach and through an open-ended approach to mathematics learning in SMK TERPADU HUTAMA. From the research results, it can be concluded that the constructivism approach is better than the open-ended approach in statistics learning because the former can encourage the development of individual’s skill in the classroom.